2019
DOI: 10.1177/2158244019843721
|View full text |Cite
|
Sign up to set email alerts
|

IT Governance and Firm Performance: Empirical Study From Saudi Arabia

Abstract: This study provides additional evidence on information technology (IT) governance and its relationship to firm performance in emerging markets. It aims primarily to determine the level of IT governance in Saudi Arabian companies; it also aims at examining the impact of IT governance on the firm performance. The study target sample is 131 companies taken from 20 sectors of the Saudi financial market; during the year 2017. The researchers have used the IT-related backgrounds of the members of the board of direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 15 publications
3
25
2
Order By: Relevance
“…The inclusion of the main effects (board composition & ownership concentration variables) in models 2 and 5 of Table 4 increases the explanatory power of variance in bank performance (∆R 2 = 0.05 *** , ∆R 2 = 0.06 *** ). The results reveal a significant positive association between board composition variables and bank performance, which is largely consistent with theoretical perspectives and empirical evidence (e.g., Al Farooque et al, 2019;Hamdan et al, 2019;Latif et al, 2020). On the other hand, ownership concentration has a negative impact on bank performance, which is in line with prior evidence ((e.g., Buallay et al, 2017;Hamdan, 2018).…”
Section: Multivariate Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The inclusion of the main effects (board composition & ownership concentration variables) in models 2 and 5 of Table 4 increases the explanatory power of variance in bank performance (∆R 2 = 0.05 *** , ∆R 2 = 0.06 *** ). The results reveal a significant positive association between board composition variables and bank performance, which is largely consistent with theoretical perspectives and empirical evidence (e.g., Al Farooque et al, 2019;Hamdan et al, 2019;Latif et al, 2020). On the other hand, ownership concentration has a negative impact on bank performance, which is in line with prior evidence ((e.g., Buallay et al, 2017;Hamdan, 2018).…”
Section: Multivariate Analysissupporting
confidence: 89%
“…In Saudi context, Hamdan et al (2019) find a positive impact of board independence on firm performance. However, Ghabayen (2012) reports a negative effect of board independence on firm performance.…”
Section: Board Composition and Firm Performancementioning
confidence: 89%
“…However, to achieve this, the hierarchical structure in the organization, that is, the supra-top relation, must be fully established. Knowledge sharing includes two or more intermediaries and has a source and destination (Hamdan et al, 2019). Therefore, providing knowledge sharing in a healthy way is important for the strategic success of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of information systems in implementing decisions properly and effectively, several studies have indicated the lack of benefit from information systems in the public institutions in the Kingdom of Saudi Arabia through the presence of some obstacles that prevent the use of information systems (Albadri, 2019;AlBar & Hoque, 2019). These obstacles lie in the lack of trained manpower capable of dealing with modern technology, the availability of appropriate software and systems for management, the lack of sufficient equipment, the absence of a computer network for the site, the lack of permanent maintenance, and the lack of training programs that carry out the process of qualifying and training these cadres (Alshuaibi, 2017;Alshumaimri et al, 2017;Hamdan et al, 2019).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…). Hamdan et al (2019) concluded that the use of information technology improves the performance of Saudi employees as this technology contributes greatly to the development of employees and improve their level of performance. There is also an urgent need to increase the participation of the national workforce in the field of information technology, and the lack of national competencies in this field is a problem that must be resolved (Al-Shammari & El-Sawy, 2020).…”
Section: Introductionmentioning
confidence: 99%